Hypoxic cancer-associated fibroblast exosomal circSTAT3 drives triple negative breast cancer stemness via miR-671-5p/NOTCH1 signaling - Lu Yang; Siyuan Zhao; Xu Liu; Yuchen Zhang; Shaorong Zhao; Xuan Fang; Jin Zhang (Journal of Translational Medicine)
Abstract Background The hypoxic tumor microenvironment, particularly hypoxia-conditioned cancer-associated fibroblasts (CAFs), drives breast cancer (BC) progression and therapy resistance. However, the molecular mechanisms linking hypoxic CAFs to BC plasticity and chemoresistance remain elusive. Methods Primary CAFs were isolated from high-grade BC tissues (Grade III) and characterized (α-SMA⁺/CD34⁻/pan-CK⁻), with normal fibroblasts (NFs) from reduction mammoplasty as controls. Hypoxic CAF-derived exosomal circSTAT3 stability was validated using RNase R resistance and actinomycin D assays. Exosomes were characterized via transmission electron microscopy (TEM), dynamic light scattering (DLS), and marker profiling (CD63⁺/TSG101⁺/Alix⁺, calnexin⁻). Functional effects of hypoxic CAF exosomes on TNBC cells (MDA-MB-231, SUM159) were assessed through proliferation/migration assays, stemness/epithelial-mesenchymal transition (EMT) marker analysis, and siRNA-mediated circSTAT3 knockdown. Mechanistic studies employed luciferase assays and RNA immunoprecipitation (RIP). Chemoresistance was evaluated by cisplatin half-maximal inhibitory concentration (IC₅₀). In vivo tumor growth and stemness enrichment were analyzed in xenografts. Clinical validation used BC tissues (n = 60) and plasma exosomes from BC patients (n = 40) versus healthy controls (n = 25). Results Hypoxic CAF-derived exosomes efficiently transferred circSTAT3 to TNBC cells, promoting proliferation, migration, EMT, and stemness marker expression. SiRNA-mediated circSTAT3 knockdown reversed these effects. Mechanistically, circSTAT3 acted as a competitive endogenous RNA (ceRNA), sponging miR-671-5p to derepress NOTCH1. Hypoxic CAF exosomes increased cisplatin IC₅₀ in TNBC cells, while circSTAT3 depletion restored chemosensitivity. In vivo, hypoxic CAF exosomes accelerated tumor growth, enriched CD44⁺/NOTCH1⁺ populations, and elevated circulating exosomal circSTAT3. Clinically, circSTAT3 was significantly upregulated in advanced BC tissues (p < 0.01) and patient plasma exosomes (p < 0.01), correlating with lymph node metastasis. Conclusion This study identifies a hypoxia-driven feedforward loop wherein CAF-derived exosomal circSTAT3 promotes TNBC stemness and chemoresistance via miR-671-5p/NOTCH1 signaling. CircSTAT3 redefines stromal-tumor crosstalk as a circRNA-driven process and serves as both a circulating non-invasive biomarker and a promising therapeutic target to disrupt stromal-mediated resistance in aggressive TNBC.